PENYULUHAN PROSPEK BETERNAK KAMBING DAN DOMBA BAGI MAYARAKAT TERDAMPAK PROYEK PLN SUMUR ADEM II KABUPATEN INDRAMAYU - Yudhi Mahmud (Abdi Wiralodra : Jurnal Pengabdian Kepada Masyarakat, 2019)
Community service activities in the form of counseling aim to provide additional knowledge and skills in doing good business and raising goats. The target audience in this PKM activity is farmers and farm laborers. This activity aims to provide knowledge and skills in order to prepare the people affected by the project development to have a business for their livelihood as a substitute for lost farming activities because the land is used for the construction of the Sumur Adem II steam power plant. The expected benefits of community service activities are as a forum for exchanging ideas between citizens and universities and providing knowledge and skills to residents in raising good goats and sheep